Weaving a new web: gregarious parasitism in Idris Förster (Hymenoptera: Scelionidae) attacking spider eggs - K. Rajmohana; Rupam Debnath; V. Sushama; Souvik Sen; K. P. Dinesh (PLoS ONE, 2025)
The present study, conducted in West Bengal, India, explored the unique ‘multi-chambered’ appearance of certain spider eggs, leading to the discovery of gregarious parasitism in the idiobiont endoparasitoid Idris Förster (Hymenoptera: Scelionidae). Little is known about the roles of parasitoid Hymenoptera in regulating spider populations. Phylogenetic analysis based on the mitochondrial cytochrome c oxidase I marker identified five distinct species of Idris. These five gregarious species, identified in association with various spider hosts across multiple locations during a two-year study, offer new insights into host-parasitoid interactions and their adaptability in different host systems. Additionally, six novel host associations between egg parasitoids and five spider species from two families are documented. Under the family Scelionidae, Idris is the second genus, after Telenomus Haliday, adapting to gregarious development. Our findings emphasize the existence of diverse trophic interactions and life strategies in nature that are yet to be documented.